Efficacy of a dual-ring wound protector for prevention of incisional surgical site infection after Whipple's procedure (pancreaticoduodenectomy) with preoperatively-placed intrabiliary stents: protocol for a randomised controlled trial. Issue 8 (21st August 2014) - Bressan, Alexsander K; Roberts, Derek J; Edwards, Janet P; Bhatti, Sana U; Dixon, Elijah; Sutherland, Francis R; Bathe, Oliver; Ball, Chad G
Abstract : Introduction: Among surgical oncology patients, incisional surgical site infection is associated with substantially increased morbidity, mortality and healthcare costs. Moreover, while adults undergoing pancreaticoduodenectomy with preoperative placement of an intrabiliary stent have a high risk of this type of infection, and wound protectors may significantly reduce its risk, no relevant studies of wound protectors yet exist involving this patient population. This study will evaluate the efficacy of a dual-ring wound protector for prevention of incisional surgical site infection among adults undergoing pancreaticoduodenectomy with preoperatively-placed intrabiliary stents. Methods and analysis: This study will be a parallel, dual-arm, randomised controlled trial that will utilise a more explanatory than pragmatic attitude. All adults (≥18 years) undergoing a pancreaticoduodenectomy at the Foothills Medical Centre in Calgary, Alberta, Canada with preoperative placement of an intrabiliary stent will be considered eligible. Exclusion criteria will include patient age <18 years and those receiving long-term glucocorticoids. The trial will employ block randomisation to allocate patients to a commercial dual-ring wound protector (the Alexis Wound Protector) or no wound protector and the current standard of care. The main outcome measure will be the rate of surgical site infection as defined by the Centers for Disease Control and Prevention criteria within 30 days of the index operation date as determined by a research assistant blinded to treatment allocation. Outcomes will be analysed by a statistician blinded to allocation status by calculating risk ratios and 95% CIs and compared using Fisher's exact test. Ethics and dissemination: This will be the first randomised trial to evaluate the efficacy of a dual-ring wound protector for prevention of incisional surgical site infection among patients undergoing pancreaticoduodenectomy. Results of this study are expected to be available in 2016/2017 and will be disseminated using an integrated and end-of-grant knowledge translation strategy. Trial registration number: ClinicalTrials.gov identifier NCT01836237 .